Effect of Instructional Supervisory Practices on Teacher Motivation in Private Secondary Schools of Lahore, Pakistan - Nasreen, Shahida; Shah, Madiha (Advances in Social Sciences Research Journal, 2019)
Research in the area of school leadership proves that effective leaders accomplish the role of instructional leaders (Zheng, 1996). The main objective of an effective principal is the supervision of classroom instructions (Hoy, & Hoy, 2006). This paper examines the effect of instructional supervisory practices of the school leaders on teacher motivation in private secondary schools of Lahore, Pakistan. Twenty four schools from three different school types (low-income schools, middle-class schools, and elite schools) were selected using stratified random sampling. A questionnaire comprising of two scales, Instructional Supervisory Practices Scale (ISPS) and Work Extrinsic and Intrinsic Motivation Scale (WEIMS), was used to collect data from 530 teachers. Descriptive as well as inferential statistics were used to obtain results. The teachers’ perceptions regarding their leaders’ instructional supervisory practices and the level of teacher motivation were determined by computing mean and standard deviation. The Pearson Correlation (r) was computed to explore the relationship between six sub-scales of instructional supervisory practices and teacher motivation. The results of the study indicated a significant positive relationship between instructional supervision and teacher motivation. It is concluded that instructional supervision significantly contributes to teacher motivation.